The concept of «possession» in the practice of the European court of human rights - Andrusiv L. (Науково-інформаційний вісник Івано-Франківського університету права імені Короля Данила Галицького, 2022)
Purpose. The purpose of the article is to reveal the concept of «property» and determine its characteristics in the case law of the European Court of Human Rights